2013
DOI: 10.1073/pnas.1220601110
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of microbial and mammalian phospholipid antigens by NKT cells with diverse TCRs

Abstract: CD1d-restricted natural killer T (NKT) cells include two major subgroups. The most widely studied are Vα14Jα18 + invariant NKT (iNKT) cells that recognize the prototypical α-galactosylceramide antigen, whereas the other major group uses diverse T-cell receptor (TCR) α-and β-chains, does not recognize α-galactosylceramide, and is referred to as diverse NKT (dNKT) cells. dNKT cells play important roles during infection and autoimmunity, but the antigens they recognize remain poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 35 publications
(38 reference statements)
1
112
0
1
Order By: Relevance
“…Previous studies with type II NKT cell hybridomas have identified several self-lipid antigens recognized by type II NKT cells, including phospholipids, β-GlcCer, and sulfatide (27,(36)(37)(38)(39)(40). Interestingly, we found that 4get + type II NKT cells are potently activated by β-GlcCer containing C12:0 and C24:1 acyl chains, suggesting that a significant proportion of type II NKT cells recognize β-GlcCer.…”
Section: Tcrβmentioning
confidence: 49%
“…Previous studies with type II NKT cell hybridomas have identified several self-lipid antigens recognized by type II NKT cells, including phospholipids, β-GlcCer, and sulfatide (27,(36)(37)(38)(39)(40). Interestingly, we found that 4get + type II NKT cells are potently activated by β-GlcCer containing C12:0 and C24:1 acyl chains, suggesting that a significant proportion of type II NKT cells recognize β-GlcCer.…”
Section: Tcrβmentioning
confidence: 49%
“…However, iNKT cells cultured with infected macrophages stimulated their antimicrobial activity, which restricted bacterial growth. The results from an early study suggested that iNKT cells directly recognize certain purified phosphatidyl inositol mannosides from Mtb (Gilleron et al, 2001), and although this could not be confirmed using synthetic antigens ; subsequent work showed that Mtb-derived phosphatidylglycerol antigens were recognized by NKT cells with diverse TCR (Tatituri et al, 2013). Mice deficient for iNKT cells had a significantly higher number of granulomas, but the number of bacteria was similar to infected, control mice.…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…A molar loading ratio (lipid to CD1d) of 200:1 was used for tetramerization studies for both mouse and human tetramers as used in other studies. 21,25 The unloaded multimer control was prepared by mixing CD1d tetramer with the carrier only.…”
Section: Lipids and Cd1d Tetramer Loadingmentioning
confidence: 99%